(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the etiological factors of mastitis, a widespread udder disease in dairy cows, with a particular focus on the effectiveness of modern diagnostic methods. A comparative analysis of Dimastin and Mastidin reagents was conducted to assess their sensitivity in detecting subclinical mastitis. The study results emphasize the importance of early detection and preventive measures in reducing economic losses and maintaining dairy productivity.